A Literature Review from Project Management Point of View on Construction Phase Delays: Study on Oil and Gas EPC Projects in Indonesia - Rifky Basalim; Tri Waluyo; Suryono Efendi (Global Management: International Journal of Management Science and Entrepreneurship, 2026)
Indonesia’s Oil and gas project construction continue face challenges notably delays that lead to underperformance. This study tries to describe the factors that causing delays in EPC oil and gas project in Indonesia from project management view. Started by overall study on cause of delays in construction worldwide, thus phenomenon on neighboring country (Malaysia) where Indonesian workers involved, then study continues with factors in Indonesia as overall, and include specific project which are South Sumatera and Sumbawa. Three main factors are always present in the cause of delays in EPC Project in Indonesia namely; contractor’s financial problem in funding the project, poor project planning and estimation leads to unrealistic determination of the duration, and ineffective change management by owner in project showed in resolving contract dispute, requirement changes, and dispute in understanding in contract articles. These factors are clearly present in EPC projects in Indonesia as main contributor in project delays together with two additional factors namely legal awareness and social community problems.